Investigation of shallow geothermal potentials for different types of ground source heat pump systems (GSHP) of Wuhan city in China. (April 2018) - Luo, Jin; Luo, Zequan; Xie, Jihai; Xia, Dongsheng; Huang, Wei; Shao, Haibin; Xiang, Wei; Rohn, Joachim
Abstract: To ensure techno-economically suitable installation of ground source heat pump (GSHP) systems, thermal and hydrogeological properties of the subsoil need to be investigated. In this paper, the geothermal potential for three types of GSHP installations in the urban area of Wuhan city is assessed based on preliminary geological investigations. The potential for shallow geothermal energy is evaluated for surface water heat pump systems (SWHP), groundwater heat pump systems (GWHP) and ground coupled heat exchanger heat pump systems (GCHP). The mapped shallow geothermal potentials provide essential information for the installation of GSHPs and for the management of geothermal resources of Wuhan city. Furthermore, the heat transfer rates for some typical configured borehole heat exchanger (BHE) are tested by field Thermal Response Tests (TRT). In order to understand the techno-economic feasibility of the GSHPs, different types of the installed systems are measured and analyzed. Highlights: Shallow geothermal potential is assessed in the urban area of Wuhan city. Geothermal potential is mapped for three types of GSHP installations. Heat transfer rates for some typical configured BHE are tested by TRTs. Installed GSHP systems are analyzed to understand techno-economic feasibility.